PRINSIP KERJASAMA DALAM WACANA JUAL BELI DI PASAR TRADISIONAL PERUMNAS TLOGOSARI SEMARANG - Astuti, Sri Puji (HUMANIKA, 2014)
The market is a meeting place for sellers and buyers. Bargaining in traditional markets is an activity that is often made between the seller and the buyer. The interaction between sellers and buyers need a language as a communication tool. How the realization of the principle of cooperation in the discourse of buying and selling in the traditional market of Perumnas Tlogosari Semarang discussed in this paper is. This study was chosen markets located in Suryo Kusumo because this market is the largest market among the three markets are in Perumnas Tlogosari Semarang. Collecting data was conducted by scrutinizing method that was developed with basic tapping technique and Advanced techniques in the form of notes and recording technique. The results showed that in the interaction of sellers and buyers comply with and violate the principle of cooperation. Compliance with the principle of cooperation intended to convey the message clearly, correctly and avoid misunderstandings. While the violation of the cooperation principle was intended to ensure the quality of goods, so merchandise sold, searching for information, the seller and the buyer is familiar, and praised the merchandise.